Preoperative Age and Prognostic Nutritional Index Are Useful Factors for Evaluating Postoperative Delirium Among Patients With Adult Spinal Deformity. Issue 7 (1st April 2019) - Oe, Shin; Togawa, Daisuke; Yamato, Yu; Hasegawa, Tomohiko; Yoshida, Go; Kobayashi, Sho; Yasuda, Tatsuya; Banno, Tomohiro; Arima, Hideyuki; Mihara, Yuki; Ushirozako, Hiroki; Yamada, Tomohiro; et al.
Abstract : Study Design: A retrospective study of postoperative delirium after adult spinal deformity (ASD) surgery. Objective: To identify the risk factors of post-ASD surgery delirium, including nutritional state before surgery. Summary of Background Data: Recently, malnutrition was reported as one of the risk factors of delirium. The prognostic nutritional index (PNI) and controlling nutritional status index (CONUT) scores are simple methods of nutritional evaluation. However, there are no reports that verify that delirium is related to the PNI and CONUT score in patients who have undergone ASD surgery. Methods: A consecutive 319 patients who underwent ASD surgery were divided into a delirium group (group D) or nondelirium group (group ND). Preoperative risk factors, including PNI, were assessed. Results: Group D consisted of 30 patients and group ND consisted of 289 patients. There was significant difference in age (group D:group ND = 73:62, P  = 0.000), serum albumin (4.2:4.3, P  = 0.028), operative time (422:395 min, P  = 0.029), PNI score (49:52, P  = 0.011), and CONUT score (1.7:1.1, P  = 0.046). Using multiple logistic regression analysis, we found significant risk factors for delirium to be age ( P  = 0.006, odds ratio = 1.11, 95% confidence interval = 1.03–1.19) and PNI ( P  = 0.003, odds ratio = 0.87, 95% confidence interval = 0.79–0.96). A receiver operating characteristic curve showed that the cut-off value of PNI and age for delirium were 49.7 and 68.5 years, respectively. Conclusion: The risk factors of postoperative delirium after ASD surgery were PNI less than 49.7 and age more than 68.5 years. Patients who undergo ASD surgery beyond these preoperative cut-off values should be cautioned about delirium and be required to provide adequate informed consent. Level of Evidence: 3 Abstract : This retrospective study evaluated risk factors for the development of delirium following adult spinal deformity surgery. Identified risk factors include a prognostic nutritional index score of <49.7 and being >68.5 years.